Addressing the soft cost challenge in U.S. small-scale solar PV system pricing. (November 2019) - O'Shaughnessy, Eric; Nemet, Gregory F.; Pless, Jacquelyn; Margolis, Robert
Abstract: Solar photovoltaic (PV) prices have fallen significantly over the past two decades. These price reductions have relied primarily on falling system hardware costs. Future reductions in PV prices—which are needed to ensure that enough PV will be deployed to meet global clean energy objectives—will require reductions in non-hardware or "soft" costs, particularly in markets with relatively high soft costs such as the United States. In this article, we draw insights from the literature on which factors affect soft costs for small-scale PV systems in the United States. The literature shows that soft costs tend to be lower for systems that are larger, installed during new construction, installed by more experienced installers, installed in more concentrated markets and in more competitive markets, installed in markets where customers receive more quotes, or installed in markets with less onerous permitting requirements. We identify three marketplace design strategies that policymakers could pursue to address the soft cost challenge in the United States and similar markets: encourage the expansion of quote platforms; encourage or require that PV system installation be integrated into the new construction and roof replacement process; and encourage the expansion of customer aggregation models such as Solarize campaigns and community solar. Highlights: Non-hardware "soft" costs are crucial for solar PV price reductions in some markets. Study explores the key factors that drive soft costs in the United States. Factors such as scale economies, market structure, and policy determine soft costs. Policymakers can implement market strategies that accelerate soft cost reductions.